Use of green area of Kastamonu: Case study of Clock Tower - SAKICI, CIGDEM (Arts and Science Press Pte. Ltd., 2018)
The aim of the study is to show which areas mainly prefered when the people want to carry out recreational activities in the Kastamonu city center and determine the appropriateness of this area for recreative activity. A questionnaire study was conducted with 100 randomly selected people in order to determine the most frequently used open green area in terms of recreational activity in Kastamonu and the results showed that 89% of the participants prefer the Clock Tower. Thus Clock Tower was determined as a research area in this study. It is revealed the current state of the Clock Tower in scope of the study, plants are used in this area and the purpose of use of these plants is determined and how frequently users use this area and the reasons for not frequent use. In addition, activities that are effected in the area and changes in mood after using the area. The second survey study was conducted on users of the area consisting of 118 people. It is revealed space  features existing at Clock Tower and events area identified after that space features that users want to be in this area and events areas. Thus, the aim of the area is to determine the users' expectations and the deficiencies and problems in this area.
Keywords: 11. Sustainability